Upregulation of LSD1 promotes migration and invasion in gastric cancer through facilitating EMT - Zhang, Jin (Cancer Manag Res, 2019)
BACKGROUND: Gastric cancer (GC) is a common malignant tumor of the digestive system. In addition, GC metastasis is an extremely complicated process. A previous study has found that lysine-specific demethylase 1 (LSD1) is abnormal expression in a variety of cancers and its overexpression correlates with aggressive disease and poor outcome. METHODS: qRT-PCR and Western blot assays were used to assess the expression of LSD1 in GC tissue samples and cell lines. Colony formation assay, CCK-8 assay, scratch-wound assay and transwell invasion, were performed to determine the effect of LSD1 on cell proliferation and migration as well as invasion in GC. RESULTS: Our results show that LSD1 was up-regulated in GC tumor tissues and cell lines, and high expression level of LSD1 was found to be positively correlated with tumor size, lymph node metastasis and pathological grade. Moreover, LSD1 promoted cell proliferation, migration and invasion of GC. In addition, LSD1 regulated E-cadherin expression through demethylating H3K4me2, thereby promoting EMT in GC. CONCLUSION: Our work indicated that LSD1 may be used as a potential target of gastric cancer.